Aplicamos una estrategia para regular nuestras emociones - Horna Avalos, Magna Edith (2020)
Emotions are reactions that we all experience: joy, sadness, fear, anger. Known to all of us but of great complexity not all of us are aware that mishandling of these emotions can lead to a blockage or even disease Emotions are affective states that we experience. Subjective reactions to the environment that are accompanied by organic changes - physiological and endocrine - of innate origin. The experience plays a fundamental role in the experience of every emotion. It is a state that comes, suddenly and abruptly, in the form of more or less violent and more or less transient crises. In humans, the experience of an emotion usually involves a set of cognitions, attitudes and beliefs about the world, which we use to assess a particular situation and therefore influence how this situation is perceived. These are conceived as behavior that can be caused by external and internal causes; that may persist even once the stimulus has disappeared and that necessarily accompanies, to a greater or lesser degree, any motivated behavior Within a few months of life we begin to express basic emotions such as fear, anger or joy. In humans they become more complex thanks to language, because we use symbols, signs and meanings. Each individual experiences an emotion in a particular way, depending on their previous experiences learning, character and the specific situation. Some of the physiological and behavioral reactions that trigger emotions are innate, while others can be acquired